Getting started with Google Cloud platform : LiveLessons (LiveLessons (Indianapolis, Ind.), 2018)
"Getting Started with Google Cloud Platform LiveLessons teaches the basics of Google Cloud so you can better understand this key platform. Chad Smith, a Google and AWS certified instructor, designed this course to help you make sense of the choices available in GCP by providing a foundational view of cloud infrastructure, and how it differs from its on-premise counterpart. Through the use of demos and concept walk-throughs, you will learn all about commonly used services and how they integrate with one another and with on-premise infrastructures. Migrating to the cloud can be a journey full of misinformation and assumptions. In addition, the differences between on-premise IT infrastructure and cloud infrastructure make it difficult to understand which services can be appropriate for workloads. Worldwide, cloud-first strategies are being replaced by cloud-only strategies, and for companies who haven't begun migration, the choices can be overwhelming."--Resource description page